2013
DOI: 10.1063/1.4827093
|View full text |Cite
|
Sign up to set email alerts
|

Resonant photoemission at the iron M-edge of Fe(CO)5

Abstract: High resolution electron kinetic energy spectra of iron pentacarbonyl (Fe(CO)5) are studied in the photon energy range of 40-90 eV. The relative yield of photolines associated with the Fe 3d level shows a Fano line shape at photon energies of 61 eV. The increase in signal from the 3d level is indicative of resonant photoemission involving 3p-3d transitions at the M edge of iron. The signature of this resonance is also present in photolines typically attributed to be mostly CO in character. We use the modulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Based on seminal photoelectron spectroscopy and investigations of Cr(CO) 6 and of CO deposited on surfaces, [79][80][81][82] the broad peak around 36 eV can be straightforwardly assigned to electron emission from the inner-valence 3σ orbital of CO bound in Fe(CO) 5 where the 3σ orbital is derived from the atomic 2s orbitals of C and O. The peak at 63 eV was determined before to arise from the emission from the Fe 3p core level in Fe(CO) 5 , 83 and we FIG. 6.…”
Section: Resultsmentioning
confidence: 98%
“…Based on seminal photoelectron spectroscopy and investigations of Cr(CO) 6 and of CO deposited on surfaces, [79][80][81][82] the broad peak around 36 eV can be straightforwardly assigned to electron emission from the inner-valence 3σ orbital of CO bound in Fe(CO) 5 where the 3σ orbital is derived from the atomic 2s orbitals of C and O. The peak at 63 eV was determined before to arise from the emission from the Fe 3p core level in Fe(CO) 5 , 83 and we FIG. 6.…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, core-excited state decay in Fe­(CO) 5 and Fe­(Cp) 2 is dominated by Auger decay, leading to ionic fragments. This is evident from the investigations of Tamenori et al, who reported ion-yield XAS at the Fe M-edge of Fe­(CO) 5 and Fe­(Cp) 2 and of Heck et al and Sistrunk et al for ion-yield Fe M-edge XAS of Fe­(CO) 5 . By resolving the nature of the various ionic fragments emitted upon X-ray irradiation, so-called partial-ion-yield spectra can be extracted. They contain information on orbital- or state-specific fragmentation of the probed sample. ,, …”
Section: Introductionmentioning
confidence: 96%
“…Figure 4 presents the XUV absorption spectrum of groundstate 5 near the Fe M-edge, compared to and characterized by A cubic polynomial fit to the baseline was subtracted from the experimental spectrum to account for contribution from a centrifugal barrier. 87,88 This subtraction is imperfect, resulting in a residual near 52 eV, which is not due to resonant core-to-valence transitions. The raw measured static absorption spectrum and baseline subtraction procedure are outlined in Section S2.1.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Figure 4. Absorption spectrum of ground-state 5.A cubic polynomial fit to the baseline was subtracted from the experimental spectrum to account for contribution from a centrifugal barrier 87,88. This subtraction is imperfect, resulting in a residual near 52 eV, which is not due to resonant core-to-valence transitions.…”
mentioning
confidence: 99%